Comparative Analysis in Terms of Islamic Viewpoint Regarding Appointment of Judges In Superior Courts of Malaysia And Pakistan - Muhammad Atiq-ur-Rehman; Noorfajri Ismail (Al-Irfan Research Center (SMC-Private) Limited Lahore-Pakistan, 2025)
Non-Indexed Publication